Prosthetic mitral valve thrombosis, malfunction, and paroxysmal mitral regurgitation. Issue 3 (19th February 2018) - Moorthy, Nagaraja; Ananthakrishna, Rajiv; Rao, Dattatreya P. V.; Manjunath, Satvic C.; Nanjappa, Manjunath C.
Abstract : Intermittent dysfunction of mechanical mitral valve prosthesis is an uncommon condition. It carries serious clinical implications if unrecognized. Here, we present a case of a 28‐year‐old female with a history of rheumatic multivalvular disease, for which she had undergone double valve replacement and tricuspid annuloplasty. Six months later, she presented with heart failure. Clinical examination revealed intermittent loss of closing clicks followed by a pansystolic murmur at the apex, suggestive of mitral prosthetic valve dysfunction. We highlight the echocardiographic findings of paroxysmal mitral valvular regurgitation secondary to prosthetic valve malfunction secondary to prosthetic valve thrombosis.